Optical polyester film
Patent Information
- Application Number
- JP2023127580
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0010】 本発明によれば、異物の発生、特に金属起因の内部異物の発生が少ない光学用ポリエステルフィルムを提供することができる。
Smart Images

Figure 2025023456000001 
Figure 2025023456000002 
Figure 2025023456000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical polyester film. [Background technology]
[0002] Polyester films have excellent mechanical properties, thermal properties, chemical resistance, electrical properties, and moldability, and are used in a variety of applications. Among polyester films, polyethylene terephthalate (hereinafter sometimes referred to as PET) films in particular have excellent transparency and processability, and are therefore ideally used as highly transparent optical films, particularly for displays and touch panels.
[0003] Generally, polyester resins, and PET in particular, are produced by producing an esterification product from a dicarboxylic acid such as terephthalic acid or an ester derivative thereof and ethylene glycol or a glycol mainly composed of ethylene glycol, and then polycondensing the esterification product at high temperature and high vacuum in the presence of a polycondensation catalyst.
[0004] Germanium compounds, titanium compounds, antimony compounds, etc. have been used as polycondensation catalysts for producing polyester resins, but antimony compounds, which are inexpensive and have excellent catalytic activity, are the most widely used. However, when antimony compounds are used as polycondensation catalysts, they tend to precipitate as insoluble metal particles during the production stage of polyester resin. This causes problems such as defects when the obtained polyester resin is molded and processed, and the precipitated antimony repels coating materials for forming optical functional layers (hard coat layers, retardation layers, etc.), causing functional defects.
[0005] In response to these problems, studies have been made as shown in the following documents. For example, Patent Document 1 discloses a technique for suppressing the generation of metallic antimony particles by reducing the amount of antimony compound added. Patent Document 2 discloses a method for producing a polyester resin using a specific amount of a manganese compound, an alkali metal compound, a phosphorus compound, and an organotitanium compound to suppress the generation of insoluble foreign matter in the polymer. Patent Document 3 discloses a technique for improving the transparency and crystallinity of a polyester resin by using a magnesium compound and a phosphorus compound as a catalyst using a germanium compound. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 3-146707 [Patent Document 2] Japanese Patent Publication No. 63-278927 [Patent Document 3] JP 2003-137992 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the method described in Patent Document 1 can suppress the generation of metal antimony particles to some extent, but it is impossible to reduce the generation to the level required for a film that requires high transparency and quality. The method described in Patent Document 2 has a problem that the activity of the titanium compound is high, and modified polymers and aggregated foreign matter are generated during the polyester polymerization reaction. The method described in Patent Document 3 has a problem that the germanium compound promotes the decomposition of the polyester resin, resulting in the generation of gelled matter and the deterioration of the heat resistance of the obtained film. In other words, when the polyester resin obtained by these methods is used, it is difficult to ensure the quality required for an optical polyester film.
[0008] An object of the present invention is to solve these problems and to provide an optical polyester film which generates less foreign matter, particularly less internal foreign matter caused by metals. [Means for solving the problem]
[0009] The present invention is intended to solve the above problems and has the following configuration. (1) The number of internal defects originating from metal components with a major axis of 10 μm to 50 μm was 38 / 250 mm 2 1. An optical polyester film, characterized in that: (2) The optical polyester film according to (1), having a metal element content of 10 ppm or more and 150 ppm or less. (3) The optical polyester film according to (1) or (2), wherein the melt resistivity of the substrate layer is from 0.1 MΩ·cm to 10 MΩ·cm. (4) The optical polyester film according to any one of (1) to (3), having a germanium content of 3 ppm or more and 100 ppm or less, a manganese content of 3 ppm or more and 40 ppm or less, and a sodium content of 4 ppm or more and 40 ppm or less. (5) The optical polyester film according to any one of (1) to (4), having a phosphorus content of 15 ppm or more and 70 ppm or less. (6) The optical polyester film according to any one of (1) to (5), which has a coating layer on at least one surface thereof. (7) The optical polyester film according to any one of (1) to (6), having a particle content of 0.01% by mass or less. (8) The optical polyester film according to any one of (1) to (7), which is for phase contrast transfer. (9) The optical polyester film according to any one of (1) to (7), which is used as a touch panel substrate. Effect of the Invention
[0010] According to the present invention, it is possible to provide an optical polyester film which is less susceptible to the generation of foreign matter, particularly internal foreign matter caused by metals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The optical polyester film of the present invention will be described in detail below. The optical polyester film of the present invention has a base layer mainly composed of a polyester resin. In the present invention, the polyester resin refers to a resin having a molecular structure in which dicarboxylic acid units and diol units are repeatedly linked by ester bonds, and the polyester film refers to a sheet-shaped molded body mainly composed of a polyester resin. The polyester resin that can be suitably used in the optical polyester film of the present invention will be described in detail later. The optical polyester film refers to a polyester film that provides some effect by transmitting, reflecting, or absorbing light, and is used in the display part of optical devices such as touch panels and displays. The main component refers to a component that is contained in an amount of more than 50 mass% and not more than 100 mass% when the total components in the object are taken as 100 mass%. The base layer mainly composed of a polyester resin refers to a layer that is mainly composed of a polyester resin and has a thickness of 23 μm or more (hereinafter, the "base layer mainly composed of a polyester resin" may be simply referred to as the "base layer"). The base layer may be a single layer or a laminated structure, and when layers that satisfy the above requirements are laminated in succession, the entire layer is treated as one base layer.
[0012] In the optical polyester film of the present invention, the number of internal defects originating from metal components and having a major axis of 10 μm or more and 50 μm or less is 38 / 250 mm. 2The following are the problems. Optical polyester films have internal defects derived from metal components, which can cause short circuits when metal sputtering such as ITO or Cu mesh processing is performed, or voids are formed from metal foreign matter, increasing internal haze and causing deterioration of transparency. Furthermore, depending on the type of metal that forms the internal defects, when it precipitates near the surface layer, the metal foreign matter may repel the coating material for forming the coating layer, causing so-called coating voids. If such problems occur, it becomes difficult to use the film in optical applications such as retardation films and touch panels.
[0013] From the above viewpoint, in the optical polyester film of the present invention, the number of internal defects originating from metal components and having a major axis of 10 μm or more and 50 μm or less is preferably 20 / 250 mm. 2 , more preferably 10 pieces / 250 mm 2 , and more preferably 9 pieces / 250 mm 2 From the above viewpoints, the number of internal defects originating from metal components is preferably as small as possible, with the lower limit being 0 defects / 250 mm. 2 The number of internal defects was 0 / 250 mm. 2 This means that the optical polyester film is 250 mm 2 This means that there are no internal defects or less than 0.5 internal defects per unit.
[0014] In the optical polyester film of the present invention, the metal element has the same meaning as a metal element generally defined, and more specifically, it refers to all elements of Group 1, and Groups 2 to 12 excluding hydrogen in the periodic table of the elements, Group 13 from the 3rd period onwards excluding boron, Group 14 from the 4th period onwards excluding carbon and silicon, Group 15 from the 5th period onwards, and Group 16 of the 6th period.
[0015] In particular, in the case of polyester film, in addition to titanium, antimony, germanium, manganese, sodium, and calcium, which are residues of the polymerization catalyst of the polyester resin, which is the main component, metal compounds derived from them are often detected. Therefore, from the viewpoint of keeping the number of internal defects derived from metal components with a major axis of 10 μm to 50 μm within the above range, it is preferable to add as little polymerization catalyst as possible to the reaction system during polymerization of the polyester resin. In addition, sodium, calcium, etc. are also contained in the washing water used in the process, so it is more preferable to use water with a high purity, such as ion-exchanged water, as the washing water rather than normal water.
[0016] The size of internal defects originating from metal components often has a major axis of about 10 μm to 50 μm. Basically, foreign matter originating from metal components is captured by the polymer filter described below during the melting to extrusion process, so the major axis of internal defects originating from metal components is often about 10 to 20 μm, but since the filtration accuracy of the polymer filter is not uniform, foreign matter with a major axis of 20 μm or more may be mixed in.
[0017] In addition to the above-mentioned methods, internal defects originating from metal components having a major axis of 10 μm or more and 50 μm or less can also be reduced by finely adjusting the filtration accuracy of the polymer filter attached to the extrusion device. From the viewpoint of reducing foreign matter that causes internal defects originating from metal components, the filtration accuracy of the polymer filter is preferably 10 μm or less, more preferably 5 μm or less. From the viewpoint of reducing foreign matter, the smaller the filtration accuracy of the polymer filter, the more preferable it is, but when a polymer filter with a filtration accuracy of 1 μm or less is used, the polymer pressure may increase, making it unsuitable for long-term membrane production. Therefore, taking into consideration the ability to withstand long-term membrane production, the lower limit of the filtration accuracy of the polymer filter is preferably 1 μm.
[0018] Here, the long diameter refers to the length of the long side of the periphery surrounding the internal defect so that the area of the internal defect is the smallest in an ellipse or rectangle. The long diameter of the internal defect and the number of internal defects with a long diameter of 10 μm to 50 μm can be measured by observation using a known micro laser scope or by its side length function. In addition, the internal defect being derived from a metal component means that the internal defect contains a metal component, and whether or not the internal defect contains a metal component can be determined by energy dispersive X-ray spectroscopy (SEM-EDX).
[0019] The optical polyester film of the present invention preferably has a metal element content of 10 ppm or more and 150 ppm or less. Here, "a metal element content of 10 ppm or more and 150 ppm or less" means that the metal element content is 10 ppm or more and 150 ppm or less when the total components of the optical polyester film are 100 mass% (the same standard applies to the amounts of other elements described later). If the metal element content exceeds 150 ppm, there is a problem that the metal component itself or a complex of the metal component and other chemical substances precipitates, thereby increasing defects in the optical polyester film. From the above viewpoint, in the optical polyester film of the present invention, the total content of the metal elements is more preferably 100 ppm or less by mass. The lower limit of the metal element content of the optical polyester film is preferably 10 ppm, more preferably 14 ppm, and even more preferably 20 ppm, from the viewpoint of the amount of catalyst preferable for promoting the polymerization reaction.
[0020] In order to achieve both reduction in thickness unevenness and improvement in productivity, the optical polyester film of the present invention preferably has a melt resistivity of the base layer of 0.2 MΩ·cm to 10 MΩ·cm. One of the factors that affect the thickness unevenness of the optical polyester film obtained by the melt casting method is the electrostatic applicability when the molten sheet-like material for obtaining the base layer of the optical polyester film is cooled and solidified on a cast drum. This electrostatic applicability can be evaluated by the melt resistivity when the base layer of the finally obtained optical polyester film is melted, and can also be substituted by the melt resistivity of the molten polyester resin that is the raw material of the base layer.
[0021] The melt resistivity is the volume resistivity of the substrate layer (or polyester resin) of the heat-melted optical polyester film. When the melt resistivity of the substrate layer is 10 MΩ·cm or less, the electrostatic applicability is good during cooling and solidification in the cast drum. Therefore, the thickness unevenness of the obtained optical polyester film is suppressed, and the film-forming speed can be increased to improve productivity. From the above viewpoint, the melt resistivity of the substrate layer of the optical polyester film is more preferably 5.0 MΩ·cm or less. In addition, the lower limit of the melt resistivity value of the substrate layer of the optical polyester film is not particularly limited, but from the viewpoint of feasibility, it is preferably 0.1 MΩ·cm, more preferably 0.2 MΩ·cm.
[0022] The method of making the melt resistivity of the base layer of the optical polyester film within the above range includes, but is not limited to, adjusting the metal element content (especially the sodium element content) in the polyester resin that is the raw material of the base layer to a suitable range, adding particles or compounds that are responsible for electrical conduction to the raw material, etc. However, if the metal element content in the raw material is increased, as described above, the heat resistance of the obtained optical polyester film may be reduced or the generation of foreign matter due to gelation may be induced. Therefore, it is preferable to apply an ionic substance that is not based on metal, and for example, a sulfonium compound, a phosphonium compound, an ammonium compound, an imidazolium compound, a pyridinium compound, or a pyrrolidinium compound can be selected as a cationic substance, and a sulfonate compound, a phosphate compound, a sulfate compound, an acetate compound, an imide compound, or the like can be selected as an anionic substance. In particular, a neutralized salt of a phosphonium compound and a sulfonate compound is preferable.
[0023] The melt resistivity of the base layer of the optical polyester film can be measured by the following method (details of the measurement method will be described later). First, the crushed optical polyester film (if it has a coating layer, the coating layer is removed before crushing) is vacuum-dried at 180°C for 3 hours, and then melted at 290°C. Thereafter, an electrode is prepared by sandwiching a "Teflon" (registered trademark) spacer between two copper plates, and this electrode is immersed in the obtained molten resin. A voltage of 5000V (V) is applied between the electrodes, and the voltage (V') is measured, and the melt resistivity (ρ) is calculated from the following formula. ρ(Ω cm)=V S R / (I V') In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).
[0024] From the viewpoints of the progress of the polycondensation reaction and the reduction of internal defects derived from metal components having a major axis of 10 μm or more and 50 μm or less, the optical polyester film of the present invention preferably has a germanium content of 3 ppm or more and 100 ppm or less, a manganese content of 3 ppm or more and 40 ppm or less, and a sodium content of 4 ppm or more and 40 ppm or less.
[0025] The optical polyester film of the present invention preferably contains germanium element in an amount of 3 ppm or more and 100 ppm or less by mass. The lower limit is more preferably 5 ppm. The upper limit is more preferably 80 ppm, and even more preferably 60 ppm. The germanium compound is used as a polymerization catalyst for polyester resin, and by setting the amount to the above lower limit or more, it is possible to proceed with the polycondensation reaction without delay. In addition, the germanium element has excellent catalytic activity, and if it is present in excess, it not only causes internal defects derived from metal components, but also contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester resin. Therefore, by satisfying the amount of germanium element below the above upper limit, it is possible to suppress various decompositions of the polyester resin, and also to reduce internal defects derived from metal components. The method for measuring the amount of germanium element in the base layer will be described later (the same applies to the amounts of other elements).
[0026] The optical polyester film of the present invention preferably contains manganese element in an amount of 3 ppm to 40 ppm by mass. The lower limit is more preferably 5 ppm. The upper limit is more preferably 30 ppm. Since manganese compounds affect the thermal decomposition of polyester resins, the heat resistance of polyester films can be improved by making the amount of manganese equal to or greater than the lower limit. In addition, since manganese element has high catalytic activity even in heat treatment at a relatively low temperature below the melting point of polyester resins, such as in a film stretching process, if it is present in excess, it not only causes internal defects derived from metal components, but also contributes to thermal decomposition, oxidative decomposition, and hydrolysis of polyesters. Therefore, by satisfying the amount of manganese element equal to or less than the upper limit, it is possible to suppress various decompositions of polyester resins and films during processing, and also to reduce internal defects derived from metal components.
[0027] The optical polyester film of the present invention preferably contains sodium element in an amount of 4 ppm or more and 40 ppm or less by mass. The upper limit is more preferably 30 ppm, and even more preferably 20 ppm. By setting the sodium element amount within the above range, the generation of foreign matter caused by sodium element is reduced, heat resistance is improved, and various decompositions of the polyester resin and film caused by thermal decomposition can be suppressed.
[0028] The polyester film of the present invention preferably has a phosphorus element content of 15 ppm or more and 70 ppm or less. The lower limit is more preferably 20 ppm, more preferably 25 ppm. The upper limit is more preferably 60 ppm, and even more preferably 50 ppm. By setting the phosphorus element content within the above range, heat resistance can be imparted to the optical polyester film.
[0029] In the optical polyester film of the present invention, metal elements that are likely to cause foreign matter are not contained as much as possible, and heat resistance is imparted to the polyester resin, which is a constituent component, by adding a compound containing manganese and sodium elements or a phosphorus compound. In particular, for sodium and phosphorus elements, phosphoric acid and sodium phosphate are preferably used from the viewpoint of suppressing deterioration of the polyester resin. That is, in the optical polyester film of the present invention, it is preferable that at least a part of the phosphorus element contained in the optical polyester film (mainly the base layer) is derived from at least one of phosphoric acid and sodium phosphate. Note that, when phosphate ions or sodium phosphate are present in the optical polyester film, the phosphorus element contained in the optical polyester film is deemed to be "derived from at least one of phosphoric acid and sodium phosphate".
[0030] In order to enhance the effect of suppressing deterioration (hydrolysis resistance) of the polyester resin of the optical polyester film, it is preferable to add phosphoric acid and sodium phosphate to the polyester resin that is the raw material of the optical polyester film, and it is more preferable to make the contents of these components closer to equal amounts in terms of molar ratio. That is, it is preferable that the optical polyester film of the present invention contains both phosphorus element derived from phosphoric acid and phosphorus element derived from sodium phosphate, and it is more preferable to make the amounts of both closer to equal amounts in terms of molar ratio. It is preferable that these phosphorus elements are contained in the base layer.
[0031] The optical polyester film of the present invention preferably has a coating layer on at least one side. By having a coating layer on at least one side, for example, it is possible to improve adhesion to a counter member. In addition, by adding particles to the coating layer, it is possible to improve handling properties. The coating layer in the present invention may also be called a functional layer or a coating layer.
[0032] The optical polyester film of the present invention preferably has a particle content of 0.01% by mass or less. The phrase "having a particle content of 0.01% by mass or less" means that the optical polyester film does not contain particles or contains particles of 0.01% by mass or less when all components constituting the optical polyester film are taken as 100% by mass. Since optical polyester films are usually required to have high transparency, it is preferable to avoid adding particles that cause a decrease in transparency as much as possible, but a small amount of 0.01% by mass or less may be added to impart running properties and handling properties. In addition, when the optical polyester film has multiple layers (for example, when it has a base layer and a coat layer), the particles may be added to any layer.
[0033] The optical polyester film of the present invention can be used for phase difference transfer. The optical polyester film for phase difference transfer is a film used as a process film for sequentially laminating an orientation layer and a phase difference layer. The small amount of internal foreign matter derived from metal can increase the inspection sensitivity, and a phase difference layer with fewer defects can be formed. In addition, some of the internal defects may be present in the surface layer. If there is a metal-derived defect in the surface layer, it may repel the orientation layer coated thereon because it has a different functional group from the surrounding polyester surface. In order to reduce the metal-derived defects present in the surface layer, it is preferable to reduce the number of metal-derived internal defects themselves.
[0034] The optical polyester film of the present invention can be used as a touch panel substrate. In touch panel substrate applications, after coating an optical adjustment layer on one side, ITO is generally sputtered, and an anti-blocking hard coat layer is coated on the other side. In either case, transparency is important, and a large amount of internal foreign matter derived from metals is recognized as a defect, and there is a possibility that the defect may cause a short circuit. The optical polyester film of the present invention can solve the above problem because the number of internal defects derived from metal components with a major axis of 10 μm to 50 μm is kept low, and the film can be suitably used as a touch panel substrate. In addition, this application requires a high level of transparency and a low level of internal defects derived from metal components, especially among optical applications, so the number of internal defects derived from metal components is kept to 9 / 250 mm. 2 The following and those not containing particles can be particularly preferably used:
[0035] Next, a method for producing the polyester resin used in the base layer of the optical polyester film of the present invention will be described, but the method for producing the polyester resin used in the base layer of the optical polyester film of the present invention is not limited thereto. The method for producing the polyester resin uses a dicarboxylic acid component or its ester and a diol component as main raw materials and consists of the following two-stage process. That is, the first stage is (A) an esterification reaction or (B) an ester exchange reaction, and the second stage is (C) a polycondensation reaction.
[0036] As raw materials for producing the polyester resin used in the base layer of the optical polyester film of the present invention, dicarboxylic acids or dicarboxylic acid esters and diols can be used, and these can also be used in combination of two or more kinds.
[0037] Examples of dicarboxylic acid components that can be used in the production of polyester resins include terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, diphenyl-4,4'-dicarboxylic acid, 5-sodium sulfoisophthalic acid, oxalic acid, succinic acid, adipic acid, sebacic acid, malonic acid, and dimer acid. Examples of dicarboxylic acid esters include the lower alkyl esters, acid anhydrides, and acyl chlorides of the above-mentioned dicarboxylic acids, and methyl esters, ethyl esters, and hydroxyethyl esters are preferably used. These components may be used alone or in combination.
[0038] In the polyester resin used in the base layer of the optical polyester film of the present invention, more preferred embodiments of the dicarboxylic acid or dicarboxylic acid ester are terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, or alkyl esters thereof, since they can give polyester resins having high melting points and which are easily processable into films, and these can also be used in appropriate combinations.
[0039] Examples of diols that can be used in the production of polyester resins include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, butanediol, 2-methyl-1,3-propanediol, hexanediol, and neopentyl glycol; alicyclic diols include saturated alicyclic primary diols such as cyclohexanedimethanol, cyclohexanediethanol, norbornanedimethanol, norbornanediethanol, tricyclodecanedimethanol, tricyclodecanediethanol, decalindimethanol, and decalindiethanol; and saturated heterocyclic primary diols containing cyclic ethers such as isosorbide. Other examples include various alicyclic diols such as cyclohexanediol, bicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentadiol, 4-cyclopentene-1,3-diol, and adamantanediol, and aromatic diols such as paraxylene glycol, bisphenol A, bisphenol S, styrene glycol, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, and 9,9'-bis(4-hydroxyphenyl)fluorene.
[0040] These components may be used alone or in combination, and polyfunctional alcohols such as trimethylolpropane and pentaerythritol may also be used other than the diol within the scope of not impairing the effects of the present invention. It is preferable to use ethylene glycol as the diol, since it is possible to fully achieve the effects of the present invention and to obtain a polyester resin that is easily processed into a film.
[0041] In the manufacturing method of the polyester resin used in the base layer of the optical polyester film of the present invention, the (A) esterification reaction step in the first step is a step of esterifying a dicarboxylic acid with a diol at a predetermined temperature until a predetermined amount of water is distilled to obtain a low polymer. When obtaining a low polymer by esterification reaction, the molar ratio of dicarboxylic acid to diol (diol / dicarboxylic acid) before the start of esterification reaction is preferably in the range of 1.05 to 1.40 from the viewpoint of esterification reactivity and heat resistance. More preferably, it is 1.05 to 1.30, and even more preferably, it is 1.05 to 1.20. By setting it in the above range, it has good reactivity and can suppress the generation of by-products such as dimers of diol, so that heat resistance can be improved.
[0042] The (B) transesterification step is a step of transesterifying a dicarboxylic acid alkyl ester with a diol until a predetermined amount of alcohol is distilled to obtain a low polymer. When a low polymer is obtained by transesterification, the molar ratio of the dicarboxylic acid alkyl ester to the diol (diol / dicarboxylic acid alkyl ester) is preferably in the range of 1.7 to 2.3 from the viewpoints of reactivity and heat resistance. By setting the ratio in the above range, the transesterification reaction can be efficiently progressed and the by-production of a dimer of the diol can be suppressed, thereby improving the heat resistance.
[0043] In the second step, the polycondensation reaction (C) is a step for obtaining a polyester resin from the low polymer obtained by the esterification reaction (A) or the transesterification reaction (B).
[0044] The polyester resin used in the base layer of the optical polyester film of the present invention can be produced by any of batch polymerization, semi-continuous polymerization and continuous polymerization.
[0045] In the method for producing the polyester resin used in the base layer, the catalyst used in the (A) esterification reaction may be a compound such as manganese, cobalt, zinc, titanium, or calcium, but it is preferable to carry out the esterification reaction without a catalyst from the viewpoint of thermal decomposition and generation of foreign matter in the polycondensation reaction stage. Here, the (A) esterification reaction proceeds sufficiently even without a catalyst due to the autocatalytic action of the carboxylic acid. In addition, a known transesterification catalyst can be used as the catalyst used in the (B) transesterification reaction. Examples of the transesterification catalyst include organic manganese compounds, organic magnesium compounds, organic calcium compounds, organic cobalt compounds, and organic lithium compounds, and specific examples thereof include carbonates, acetates, benzoates, oxides, and hydroxides, but are not limited thereto.
[0046] In the manufacturing method of the polyester resin used in the base layer of the optical polyester film of the present invention, when compounds containing germanium, manganese, and sodium are used, these compounds may be added at any stage of the (A) esterification reaction or (B) ester exchange reaction process, or the subsequent (C) polycondensation reaction process. However, by adding these compounds before the end of the polycondensation reaction, it is possible to improve heat resistance and obtain a polyester resin with reduced foreign matter.
[0047] In the manufacturing method of the polyester resin used in the base layer of the optical polyester film of the present invention, a compound containing germanium, manganese, and sodium is added before the end of the polycondensation reaction, and the contents of the germanium element and the manganese element are 3 ppm or more and 100 ppm or less, the manganese content is 3 ppm or more and 40 ppm or less, and the sodium content is 4 ppm or more and 40 ppm or less, respectively, in the finally obtained polyester resin, so that it is easy to satisfy the germanium element content of 3 ppm or more and 100 ppm or less, the manganese content of 3 ppm or more and 40 ppm or less, and the sodium content of 4 ppm or more and 40 ppm or less in the polyester film.
[0048] In the method for producing a polyester resin for a base layer, it is preferable to add germanium element so that the content is 3 ppm or more and 100 ppm or less relative to the mass of the polyester resin. The lower limit is more preferably 5 ppm. The upper limit is more preferably 80 ppm, and even more preferably 60 ppm. The germanium compound is used as a polymerization catalyst for polyester, and by setting the content to the above lower limit or more, it is possible to proceed with the polycondensation reaction without delay. In addition, the germanium element has excellent catalytic activity, and if it is present in excess, it contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester resin. Therefore, by satisfying the amount of germanium element below the above upper limit, it is possible to suppress various decompositions of the polyester resin. Examples of compounds containing germanium element used in the production of polyester resin include, but are not limited to, germanium oxide and germanium alkoxide. It should be noted that these compounds can be used alone or in combination.
[0049] The polyester resin for the base layer preferably contains manganese element in an amount of 3 ppm or more and 40 ppm or less relative to the mass of the polyester resin. The lower limit is more preferably 5 ppm. The upper limit is more preferably 30 ppm. By making the manganese element amount equal to or more than the lower limit, it is possible to improve the heat resistance of the polyester resin. In addition, the manganese element has high catalytic activity even in heat treatment at a relatively low temperature below the melting point of the polyester resin, such as in a film stretching process, and contributes to thermal decomposition, oxidative decomposition, and hydrolysis of the polyester resin. Therefore, by satisfying the manganese element amount equal to or less than the upper limit, it is possible to suppress various decompositions of the polyester resin in the processing process.
[0050] The compound containing manganese element used in the production of polyester resin is not particularly limited, but examples thereof include manganese acetate, manganese nitrate, manganese chloride, manganese sulfate, and their hydrates, and manganese acetate is preferred from the viewpoint of solubility and catalytic activity. These compounds can be used alone or in combination. The form of the compound containing manganese element when added may be any of powder, slurry, and solution, and it is preferred to add it as a solution from the viewpoint of dispersibility. The solvent used in this case is preferably the same as the diol component of the polyester resin. For example, when the polyester resin is PET, it is particularly preferred to use ethylene glycol as the solvent.
[0051] In addition, it is preferable to add sodium element to the polyester resin for the base layer so that the content is 4 ppm or more and 40 ppm or less relative to the mass of the polyester resin. The upper limit is more preferably 30 ppm, and even more preferably 20 ppm. When the sodium element content is 40 ppm or less, metal agglomerated foreign matter is reduced and deterioration of the heat resistance of the polyester resin is mitigated. When the sodium element content is 4 ppm or more, deterioration of the heat resistance of the polyester resin is mitigated. That is, by setting the sodium element content in the above range, heat resistance is improved and deterioration of the polyester resin caused by thermal decomposition can be suppressed.
[0052] The compound containing sodium element used in the production of the polyester resin is not particularly limited. For example, sodium phosphate, hydroxide, acetate, carbonate, nitrate, chloride, etc. can be used. From the viewpoint of heat resistance, the compound containing sodium element is more preferably sodium phosphate. Examples of sodium phosphate include sodium dihydrogen phosphate, disodium hydrogen phosphate, and trisodium phosphate. From the viewpoint of heat resistance, sodium dihydrogen phosphate is particularly preferable. In addition, a plurality of sodium phosphates may be used in combination.
[0053] In the production of the polyester resin for the base layer, it is preferable to use the sodium phosphate in combination with another compound containing phosphorus, and it is particularly preferable to mix the sodium phosphate and phosphoric acid as a buffer solution. By adding the sodium phosphate and phosphoric acid as a buffer solution, it is possible to achieve better heat resistance.
[0054] In addition, an alkali metal compound other than sodium phosphate may be used in combination within the range of the above-mentioned sodium element content. For example, by using potassium hydroxide in combination, the melt resistivity of polyester required for electrostatic application film formation in film production can be reduced, thereby improving productivity.
[0055] The compound containing sodium element may be added in any form such as powder, slurry, or solution, and is preferably added as a solution from the viewpoint of dispersibility. The solvent used in this case is preferably the same as the diol component of the polyester resin, and when the polyester resin is PET, it is particularly preferable to use ethylene glycol.
[0056] The polyester resin for the base layer is preferably added with phosphorus element so that the content is 15 ppm or more and 70 ppm or less relative to the mass of the polyester resin. The lower limit is more preferably 20 ppm, and even more preferably 25 ppm. The upper limit is more preferably 60 ppm, and even more preferably 50 ppm. By setting it within the above range, heat resistance can be imparted to the polyester resin.
[0057] In the method for producing the polyester resin for the base layer, it is preferable to further deactivate the polyester resin obtained after the polycondensation reaction. It is known that the catalytic activity of the polyester resin obtained by polycondensation reaction using a germanium catalyst is deactivated by treating it under relatively mild conditions such as with hot water. By losing the catalytic activity, when the polyester resin is used in the subsequent film formation process, the thermal decomposition caused by the polycondensation catalyst is suppressed, and it is possible to obtain a polyester film with excellent heat resistance.
[0058] The deactivation treatment of the polyester resin can be carried out with various solutions such as water, phosphorus compounds, and ammonia compounds. Examples of phosphorus compounds include, but are not limited to, phosphate esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, dimethyl phosphate, diphenyl phosphate, methyl phosphate, and ethyl phosphate, and aqueous solutions or solutions of phosphorus compounds such as phosphoric acid and polyphosphoric acid, and the polyester resin is contacted with the phosphorus compounds. Examples of ammonia compounds include triethylamine, tetraethylammonium hydroxide, and tetra-n-butylammonium hydroxide. The temperature at which the polyester resin is contacted with these treatment solutions and treated is preferably 20°C or higher and 120°C or lower, more preferably 40°C or higher and 100°C or lower, and even more preferably 50°C or higher and 100°C or lower. The treatment time is preferably 30 minutes or longer and 24 hours or shorter, and more preferably 1 hour or longer and 12 hours or shorter.
[0059] In the method for producing the polyester resin for the base layer, for example, germanium element and phosphorus element are distilled off during the polycondensation reaction, so it is preferable to adjust the amount of addition taking into consideration the amount of distillation so as to obtain the above-mentioned amount of element.
[0060] In the method for producing a polyester resin for a base layer, when the method is carried out via (A) an esterification reaction, it is preferable to add a glycol component such as ethylene glycol after the esterification reaction and before the compound containing sodium is added. More preferably, it is added after the compound containing manganese is added and before the compound containing sodium is added. Since the low molecular weight polyester resin obtained by the esterification reaction has a higher degree of polymerization than the low molecular weight polyester resin obtained by the transesterification reaction, it is difficult to disperse and tends to become a foreign body when a sodium phosphate salt is used. Therefore, by adding a glycol component such as ethylene glycol and lowering the degree of polymerization by depolymerization, the foreign body can be suppressed. At this time, if a compound containing manganese is present, the depolymerization can be performed more efficiently.
[0061] The amount of glycol components such as ethylene glycol to be added is preferably 0.05 to 0.5 times by mol relative to the total amount of acid components, and more preferably 0.1 to 0.3 times by mol. By adjusting the amount within the above range, the polymerization time is not delayed due to a temperature drop in the polymerization system, and the sodium phosphate salt can be prevented from becoming a foreign substance.
[0062] It is preferable to stir the reaction system during and after the addition of the compounds containing germanium, manganese, and sodium, as stirring can disperse the additives more uniformly.
[0063] In addition, in the method for producing a polyester resin for a base layer, solid-phase polymerization may be performed to obtain a polyester resin having a high molecular weight. The solid-phase polymerization is performed by heating the polyester resin under an inert gas atmosphere or under reduced pressure, although the apparatus and method are not particularly limited. The inert gas may be any gas that is inactive to the polyester resin, and examples of such gas include nitrogen, helium, and carbon dioxide gas. From the viewpoint of economy, nitrogen is preferably used. In addition, under reduced pressure conditions, it is advantageous to achieve a higher vacuum, since the time required for the solid-phase polymerization reaction can be shortened, and specifically, it is preferable to maintain the pressure at 110 Pa or less. In addition, when performing a deactivation treatment, it is preferable to perform the deactivation treatment after the solid-phase polymerization in order to perform the solid-phase polymerization efficiently.
[0064] When the polyester resin is processed into the base layer of the polyester film, one or more of various additives, such as colorants including pigments and dyes, lubricants, antistatic agents, flame retardants, ultraviolet absorbers, antibacterial agents, nucleating agents, plasticizers, and release agents, may be added within a range that does not impair the effects of the present invention.
[0065] Specific examples of the method for producing a polyester resin for obtaining the base layer of the polyester film of the present invention will be given below, but the present invention is not limited thereto.
[0066] A slurry of terephthalic acid and ethylene glycol (1.15 times the molar amount of terephthalic acid) is gradually added to an esterification reactor containing dissolved bishydroxyethyl terephthalate (BHT) at 240-260°C to allow the esterification reaction to proceed. The temperature in the reaction system is controlled to 245-250°C, and the esterification reaction is terminated when the reaction rate reaches 95%.
[0067] The esterification product thus obtained is transferred to a polymerization apparatus, and a manganese compound and a germanium compound are added. Then, ethylene glycol is added, and phosphoric acid and sodium phosphate are added. During these operations, it is preferable to keep the temperature in the system at 240 to 255°C so that the esterification product does not solidify.
[0068] Thereafter, the temperature inside the polymerization apparatus is gradually raised to 260-300°C, while the pressure inside the polymerization apparatus is gradually reduced from normal pressure to 133 Pa or less to distill off ethylene glycol. When a predetermined stirring torque is reached, the reaction is terminated, the reaction system is returned to normal pressure with nitrogen gas, and the molten polyester is discharged into cold water in the form of strands and cut to obtain a polyester resin.
[0069] The polyester resin thus obtained has excellent heat resistance and produces little gel composition or low molecular weight substances such as terephthalic acid during melt molding or processing, and can be suitably used for polyester films that require high quality, particularly for optical film applications, i.e., the base layer of the polyester film of the present invention.
[0070] The substrate layer in the optical polyester film of the present invention is not particularly limited as long as it is mainly composed of polyester resin, but is preferably a biaxially oriented polyester film. The term "biaxial orientation" as used herein refers to a film that shows a biaxially oriented pattern in wide-angle X-ray diffraction. A biaxially oriented polyester film can generally be obtained by stretching an unstretched polyester sheet by about 2.5 to 5.0 times in each of the longitudinal and transverse directions of the sheet, and then subjecting the sheet to heat treatment to complete the crystal orientation. The longitudinal direction refers to the direction in which the film runs during the manufacturing process (in the case of a film roll, this corresponds to the winding direction, also called the vertical direction), and the transverse direction (also called the horizontal direction) refers to the direction perpendicular to the longitudinal direction within the film plane.
[0071] The substrate layer in the optical polyester film of the present invention is obtained by melt-extruding a resin composition mainly composed of a polyester resin and forming it into a sheet. The substrate layer of the polyester film of the present invention may be composed of one layer in the thickness direction, or may have multiple layers. A substrate layer having multiple layers can be obtained, for example, by supplying molten polyester resin from multiple extruders, stacking them in the thickness direction, and then cooling and solidifying them to form a sheet.
[0072] The base layer in the optical polyester film of the present invention preferably has an internal haze of 0.5% or less, more preferably 0.3% or less. Haze is a value indicating the proportion of light scattered through the polyester film, and the lower the haze, the less light is scattered, and the polyester film has a more transparent and clear appearance. Light scattering is mainly divided into scattering due to the surface shape of the polyester film (external scattering) and scattering due to additives, impurities, cavities, etc. inside the polyester film (internal scattering), and the scattering ratio due to the former is called external haze, and the scattering ratio due to the latter is called internal haze. The internal haze can be measured using a known haze meter, the details of which will be described later.
[0073] Optical polyester films used in displays and the like have various processing such as a hard coat layer, an electrode layer, a refractive index adjustment layer, and a transparent adhesive layer on their surfaces, so that the external haze, which is scattering due to the surface shape, can be adjusted by the processing configuration. On the other hand, the internal haze due to internal scattering cannot be adjusted by processing, so it is a very important characteristic for an optical base film. Therefore, if the internal haze of an optical polyester film is 0.5% or less, the proportion of light that is scattered through the optical polyester film is reduced, and the transparency and definition of the display are improved.
[0074] The method of adjusting the internal haze to a desired value can be a method of not mixing foreign matter that scatters light, such as additives, impurities, or air bubbles, into the film, or a method of biaxially orienting an optical polyester film and appropriately controlling the crystallinity. More specifically, this can be achieved by making the amount of additives, particularly metal-based additives such as catalysts, in the polyester resin used in the base layer 150 ppm or less, or by using a specific catalyst species or phosphorus-based additive in an appropriate amount as described above. In addition, other preferred methods include properly storing and weighing the polyester resin to prevent foreign matter from being mixed in, and performing high-precision filtration with a filtration accuracy of 10 μm or less during the melt extrusion process of the polyester resin. These methods can be used in appropriate combination.
[0075] In the case where an additive such as a lubricant is used in the optical polyester film of the present invention in order to reduce the slip coefficient and improve the handling, it is preferable to reduce the amount of the additive as much as possible. As a method for efficiently reducing the slip coefficient with a small amount of additive, it is preferable to localize the additive on the film surface as much as possible. Specifically, a method in which a base layer is configured by laminating a plurality of layers in the thickness direction and an additive is added only to the layer forming the film surface, or a method in which a coating layer containing an additive is provided on the polyester base layer, etc. can be mentioned. In particular, it is preferable that the optical polyester film of the present invention has a coating layer on at least one surface of the base layer, since it is possible to relatively easily add functions such as improving adhesion with a functional layer provided on the polyester film and imparting antistatic properties.
[0076] In the optical polyester film of the present invention, the method of laminating the coating layer is not particularly limited. For example, a so-called off-line coating method can be used in which a coating layer is formed by unwinding a film, coating and drying the film in a separate process from the film production process, or a so-called in-line coating method can be used in which a resin is extruded by an extruder, the resin is formed into a sheet-like film, and coating is performed during the film production process to obtain a coated film in one go.
[0077] It is preferable to add a lubricant to the coating layer of the present invention in order to improve the slipperiness of the film surface and improve the handling. The lubricant used is not particularly limited as long as it does not impair the film properties, but examples thereof include inorganic particles such as colloidal silica, titanium oxide, aluminum oxide, zirconium oxide, calcium carbonate, carbon black, and zeolite particles, and organic particles such as acrylic particles, silicone particles, polyimide particles, "Teflon" (registered trademark) particles, crosslinked polyester particles, crosslinked polystyrene particles, crosslinked polymer particles, and core-shell particles. Any of these particles may be used, or a combination of two or more types may be used. The number average primary particle size of these particles (hereinafter, sometimes simply referred to as the average primary particle size) is preferably within the range of 50 to 1000 nm. Here, the average primary particle size is the average particle size of primary particles defined in JIS H7008 (2002) as particles generated by the growth of a single crystal nucleus. The amount of particles added should be appropriately adjusted and designed depending on the thickness of the lubrication layer, resin composition, average primary particle size, desired lubricity, and application, but is preferably in the range of 0.05 to 8 mass%, and more preferably in the range of 0.1 to 5 mass%, when the total components forming the lubrication layer are taken as 100 mass%.
[0078] The coating layer of the optical polyester film of the present invention may contain known polyester, acrylic, urethane, epoxy, and other resins, either alone or in combination, in order to provide various functions such as retaining lubricant particles, improving adhesion to other functional layers, and sealing oligomers precipitated from the film. Furthermore, a melamine, oxazoline, or carbodiimide crosslinking agent may be contained.
[0079] Next, the method for producing the optical polyester film of the present invention will be described taking as an example a case where polyethylene terephthalate (PET) is used as the polyester forming the base layer, but the present invention is not limited thereto.
[0080] PET pellets with an intrinsic viscosity of 0.5 to 0.8 dl / g that constitute the base polyester film are vacuum dried, fed into an extruder and melted at 260 to 300°C. After removing foreign matter with a filter, the pellets are extruded into a sheet from a T-shaped die, and wrapped around a mirror-finished casting drum with a surface temperature of 10 to 60°C using an electrostatic casting method, and cooled and solidified to produce an unstretched PET film. This unstretched film is stretched 2.5 to 5.0 times in the machine direction between rolls heated to 70 to 100°C to obtain a uniaxially stretched film. Note that some or all of the PET pellets may contain recycled raw materials, which will be described later.
[0081] A water-based coating agent constituting a coating layer is applied to at least one side of this uniaxially stretched film. Then, the widthwise ends of the uniaxially stretched film coated with the water-based coating agent are held by clips of a tenter device and introduced into a drying zone, where the coating agent is dried and then heated at a temperature of 70 to 150°C, and then continuously stretched 2.5 to 5.0 times in the transverse direction in a heating zone of 70 to 150°C, followed by heat treatment for 5 to 40 seconds in a heating zone of 200 to 240°C, and then passing through a cooling zone of 100 to 200°C to obtain an optical polyester film in which a coating layer is laminated on a substrate layer in which crystal orientation has been completed. During the heat treatment, a 3 to 12% relaxation treatment may be performed as necessary. In the above example, the biaxial stretching is performed by sequential longitudinal and transverse stretching, but the stretching may be performed by simultaneous biaxial stretching, and after longitudinal and transverse stretching, the stretching may be performed again in either the longitudinal or transverse direction. However, in the case of simultaneous biaxial stretching, since it is not possible to apply a water-based coating material to a uniaxially stretched film, when an in-line coating method is employed, it is advisable to apply a water-based coating material to an unstretched film.
[0082] Thereafter, the both ends in the width direction held by the clips are cut and removed from the obtained optical polyester film, and the film is cut to a desired width and wound up. The cutting and removal of both ends in the width direction and the cutting to a desired width can be performed by a device capable of cutting the traveling optical polyester film parallel to the longitudinal direction, such as a known slitter. EXAMPLES
[0083] Next, the present invention will be described using examples, but the present invention is not limited to the embodiments described below.
[0084] [Methods for measuring physical properties and evaluating various characteristics] (1) Internal haze of the film The following measurements were made using a haze meter (HGM-2DP) manufactured by Suga Test Instruments Co., Ltd. A sample was cut to a size of 60 mm x 30 mm, and inserted into a quartz cell filled with tetralin and having an optical path length of 1 cm. The haze was calculated from the measured value.
[0085] (2) Quantitative determination of germanium, manganese, phosphorus, sodium, and metal elements 5 g of the sample (ground material of polyester resin or base layer of optical polyester film) was placed on a platinum plate, melted and carbonized with an electric heater, and then completely incinerated in an electric furnace (700 °C) for 1.5 hours. The incinerated material was then dissolved in 5 mL of concentrated hydrochloric acid, and pure water was added to make a 10% hydrochloric acid solution to prepare a measurement sample. The above solution was used as the measurement sample and quantified by atomic absorption spectrometry (frame: acetylene-air, acetylene-dinitrogen monoxide for germanium element only). The atomic absorption spectrophotometer used was Hitachi High-Tech Science's "ZA-3300". The method for obtaining ground material of the base layer from optical polyester film is as follows. Since the film before the coating layer was removed did not contain potassium element, when potassium element was detected in this measurement, it was determined to be derived from the residue when the functional layer was removed, and was excluded from the subject of quantification.
[0086] [Method for obtaining pulverized material of substrate layer from optical polyester film] The optical polyester film is crushed to a size of 0.5 cm to 3.0 cm, and then placed in a 7% by mass aqueous solution of potassium hydroxide (pH: 14), and washed with stirring for 1 hour at a temperature of 85° C. After washing, the crushed material is washed with water and dried to obtain a crushed material of the washed base layer.
[0087] (3) Intrinsic viscosity (IV) of polyester resin The polyester resin was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula (C), and the obtained value was taken as the intrinsic viscosity (IV). ηsp / C=[η]+K[η] 2 ·C ···Formula (C) (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).)
[0088] (4) Melting resistivity Two copper plates were used as electrodes with a "Teflon" (registered trademark) spacer between them to create an electrode, which was then submerged in polyester resin that had been melted at 290°C and vacuum-dried (conditions: 180°C, 3 hours) or ground material of the base layer of optical polyester film, and a voltage of 5000 V (V) was applied between the electrodes, the voltage (V') was measured, and the melt resistivity (ρ) was calculated from the following formula. The method for obtaining ground material of the base layer from the optical polyester film is as shown in (2). ρ(Ω cm)=V S R / (I V') (In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).
[0089] (5) Evaluation of foreign matter in polyester resin 0.1 mg of polyester resin sandwiched between two cover glasses was melted on a hot plate heated to 290°C to prepare a preparation on which a thin polymer film was formed. This preparation was observed under an optical microscope (Olympus Corporation: BX50, 400x, dark field), and all observable light spots were counted and evaluated according to the following criteria (A and B were considered pass, and C was considered fail). A: 0~5 pieces / 0.1mg B: 6~9 pieces / 0.1mg C: 10 or more / 0.1mg.
[0090] (6) Heat resistance evaluation of polyester resin Using a press machine, the polyester resin was molded to a thickness of 100 μm and a width of 5 cm × 5 cm to produce three pressed films (press machine: 15-ton, four-column single-acting upward-moving press machine manufactured by Gonno Hydraulic Machinery Co., Ltd.). The three obtained pressed films were subjected to a heat treatment at 230°C for 30 minutes in a hot air dryer, and then the three pressed films were folded in half while overlapping each other. The heat resistance was evaluated according to the following criteria based on the number of pressed films that broke at this time (A and B were considered to be acceptable, and C was considered to be unacceptable). A: Not a single piece broke. B: One or two sheets are broken. C: All three pieces broke.
[0091] (7) Number of internal defects in optical polyester film One side of the optical polyester film was filled in with a black oil-based pen (Teranishi Chemical Industry Co., Ltd. Magic Ink No. 500 Black M500-T1). Then, using a Keyence laser microscope VK-X100, an area of 10 mm in width and 25 mm in length was observed from the opposite side to the filled side at a magnification of 200 times (eyepiece lens 20 times, objective lens 10 times), and the number of internal defects was evaluated based on the number of foreign objects with a major axis size of 10 μm or more. The major axis size was measured using the image processing built into the VK-X200.
[0092] (8) Analysis of internal defects The analysis of the foreign matter was carried out using SEM-EDX. Among the foreign matters detected in (7), those with a major axis size of 50 μm or less were analyzed using SEM-EDX, and the number of metallic foreign matters detected was counted.
[0093] (9) Evaluation as a touch panel substrate The following raw materials were diluted with propylene glycol monomethyl ether (PGMA) and mixed, and each raw material was dispersed in a solvent to prepare a coating material with a non-volatile content of 25.5% by mass. The coating material obtained here was applied to the coating layer of an optical polyester film so that the film thickness after drying would be 1.0 μm. After that, the solvent in the coating film was removed in a drying oven set at 80°C, and then the coating material was dried using a UV treatment device with an integrated light dose of 400 mJ / cm. 2 The coating film was cured by irradiating it with ultraviolet light so that an optical functional layer was formed. An ITO protective film ("SUNYTECT" (registered trademark) NSA33T, manufactured by San-A Chemical Co., Ltd.) was attached to the other surface (plain surface) of the optical polyester film. [raw materials] Reactive group decorated colloidal silica (dispersion medium: propylene glycol monomethyl ether acetate, non-volatile content: 40% by weight): 100 parts by weight Dipentaerythritol hexaacrylate: 48 parts by mass 1,6-Hexanediol diacrylate: 12 parts by mass Photopolymerization initiator (1-hydroxycyclohexyl phenyl ketone): 2.5 parts by mass A transparent conductive layer was disposed on the surface of the optical functional layer by sputtering to produce a transparent conductive film. Specifically, a target of indium oxide with 5% by mass of tin oxide was used to form a film in a mixed atmosphere of 98% by volume of argon gas and 2% by volume of oxygen gas to produce a transparent conductive layer made of a composite oxide of indium oxide and tin oxide. The resulting laminate was then heated in an oven at 140°C for 90 minutes to produce a transparent conductive film. The transparency and visibility of the resulting film were evaluated according to the following criteria. A: Both transparency and visibility were good. B: No problem in practical use, but poor in transparency and visibility. C: Transparency and visibility were poor to a level that was problematic for practical use.
[0094] (10) Missing layers in retardation layer A photo-alignment layer composition was prepared by dissolving a photo-alignment material having a polyvinyl cinnamate (PVCi) group in a mixed solvent containing isobutyl acetate to a solid content ratio of 5% by mass, so that the film thickness after curing would be 200 nm, and the composition was applied to an optical polyester film by a die coating method. The film was then dried for 2 minutes in a dryer adjusted to 100°C to evaporate the solvent and thermally cure the composition to form a photo-alignment layer. Next, an integrated light dose of 40 mJ / cm was applied to this photo-alignment layer. 2 A patterned alignment layer with a thickness of 200 nm was formed by irradiating polarized ultraviolet light in a direction parallel to the conveying direction of the original roll so that the alignment layer was formed. Next, a liquid crystal composition of photopolymerizable nematic liquid crystal (solid content 30%, methyl isobutyl ketone (MIBK) was used as a solvent) was applied by a die coating method on the formed patterned alignment layer, dried, and then polymerized by ultraviolet irradiation to form a retardation layer (refractive index 1.60) with a thickness of 1 μm. Finally, the PET film was peeled off to obtain a retardation film. White LED light was irradiated from the alignment layer side of the obtained retardation film, and a polarizing plate and a CCD camera were installed on the opposite side in that order, and the CCD camera was used to detect the places where light escapes. The alignment layer and the polarizing plate were installed so that the alignment axes were crossed Nicols (the alignment axes were perpendicular), and the places where light escapes were not crossed Nicols, that is, coating omissions. The number of such cases was evaluated according to the following criteria (A and B were considered to be pass, and C was considered to be fail). A: The number of coating defects is 0.01 / m 2 The results were as follows. B: The number of coating defects is 0.01 / m 2 More than 0.10 pieces / m 2 The results were as follows. C: The number of coating defects is 0.10 / m 2 exceeded.
[0095] (11) Surface observation of retardation layer The surface of the retardation film prepared above was observed with a Keyence laser microscope VK-X100 to check for the presence or absence of particles after transfer. If there are any irregularities, the incidence accuracy of light will change, and there is a possibility that the retardation film will not be able to fully demonstrate its performance.
[0096] [Reference Example 1] Preparation of polyester resin 1 A slurry consisting of 86 parts by mass of terephthalic acid and 37 parts by mass of ethylene glycol (1.15 times the molar amount relative to terephthalic acid) was gradually added to an esterification reactor containing 105 parts by mass of bishydroxyethyl terephthalate (hereinafter referred to as BHT) melted at 250°C, and the esterification reaction was allowed to proceed. The temperature in the reaction system was controlled to 245-250°C, and the esterification reaction was terminated when the reaction rate reached 95%. 105 parts by mass (equivalent to 100 parts by mass of PET) of BHT was charged in a molten state from the esterification reactor into the polymerization apparatus, and the temperature was set to 255°C. An ethylene glycol solution of manganese acetate tetrahydrate (23 ppm as manganese element relative to the mass of polyester resin) and germanium dioxide (45 ppm as germanium element relative to the mass of polyester resin) were added. Next, an ethylene glycol solution of phosphoric acid (19 ppm as phosphorus element relative to the mass of polyester resin) and sodium dihydrogen phosphate dihydrate (14 ppm as sodium element relative to the mass of polyester resin, 19 ppm as phosphorus element) was added. Then, an ethylene glycol solution (20 ppm as phosphorus element relative to the mass of polyester resin) in which paratoluenesulfonic acid and tetrabutylphosphonium hydroxide were mixed in equimolar amounts was added. For germanium dioxide, an ethylene glycol solution was used in which ethylene glycol was added after completely dissolving it in a 20% by mass aqueous solution of tetraethylammonium hydroxide. Then, the temperature inside the polymerization apparatus was gradually raised to 290°C, and the pressure was reduced from normal pressure to 133 Pa or less, and polymerization reaction was carried out until a predetermined stirring torque was shown at 290°C. After the polymerization reaction was completed, the reaction system was returned to normal pressure with nitrogen gas, and the molten polyester in the polymerization apparatus was discharged in the form of strands while being cooled in a water tank filled with ion-exchanged water, and then cut to obtain polyester resin 1 in the form of pellets. The properties of the obtained polyester resin 1 are shown in Table 1.
[0097] [Reference examples 2~9] Polyester resins 2 to 9 were obtained in the same manner as in Reference Example 1, except that the amounts of germanium, manganese, sodium, and phosphorus in the polyester resin were adjusted as shown in Tables 1 and 2. The properties of each of the obtained polyester resins are shown in Table 1.
[0098] [Reference examples 10-14] Polyester resins 10 to 14 were obtained in the same manner as in Reference Example 1, except that an ethylene glycol solution containing an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide was not used (Reference Examples 10, 12, and 14), and the amount of phosphorus element was changed as shown in Table 1. The properties of each of the obtained polyester resins are shown in Tables 1 and 2.
[0099] [Reference examples 15, 16] Polyester resins 15 to 16 were obtained in the same manner as in Example 1, except that an ethylene glycol solution of an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide was added, followed by an ethylene glycol slurry of colloidal silica having an average particle size of 1 μm, so that the silica content was 0.005% by mass (Reference Example 15) or 0.2% by mass (Reference Example 16) relative to the polyester resin. The properties of each of the obtained polyester resins are shown in Table 2. [Reference examples 17-19] Polyester resins 17 to 19 were obtained in the same manner as in Reference Example 1, except that an ethylene glycol solution of tetra-n-butoxytitanium (10 ppm as titanium element relative to the mass of the polyester resin (Reference Example 17)) or an ethylene glycol slurry of diantimony trioxide (70 ppm or 110 ppm as antimony element relative to the mass of the polyester resin (Reference Examples 18 and 19, respectively)) was added instead of germanium dioxide. The properties of each of the obtained polyester resins are shown in Table 2.
[0100] [Reference examples 20, 21] A polyester resin was obtained in the same manner as in Reference Example 1 (Reference Example 20) or Reference Example 18 (Reference Example 21), except that normal water was used instead of ion-exchanged water when washing the polyester resin. The properties of each of the obtained polyester resins are shown in Table 2.
[0101] [Reference Example 22] Preparation of water-soluble polyester resin (A) for coating Under a nitrogen gas atmosphere, 88 molar parts of terephthalic acid as a dicarboxylic acid component, 12 molar parts of sodium 5-sulfoisophthalate, and 140 molar parts of ethylene glycol as a glycol component were charged into an ester exchange reactor, and 100 parts by mass of tetrabutyl titanate (catalyst) was added to this in an amount of 1 million parts by mass of the total dicarboxylic acid components. An esterification reaction was carried out at 160 to 240°C for 6 hours, and then the distillate was removed until the reaction product became transparent. Then, a polycondensation reaction was carried out under reduced pressure at 220 to 280°C to obtain polyester resin (A).
[0102] [Reference Example 23] Method for producing polyester film The polyester resin was dried in a vacuum at 160°C for 4 hours, and then fed to an extruder and melt-extruded at 285°C. After filtering through a filter with an average aperture of 5μm made by sintering and compressing stainless steel fibers, and then through a filter made by sintering stainless steel powder with an average aperture of 14μm, the resin was extruded into a sheet from a T-shaped die, and was wrapped around a mirror-finished casting drum with a surface temperature of 25°C at a casting speed of 30m / min using an electrostatic casting method, and cooled and solidified. This unstretched film was preheated to 80°C with a preheating roll, and then stretched 3.1 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls while heating it to 95°C from above and below using a radiation heater, and then cooled to 25°C with a cooling roll to obtain a uniaxially oriented (uniaxially stretched) film. Next, the following coating liquid was applied to one surface of the uniaxially stretched film, and the coating liquid was measured to a thickness of 6μm using a metering wire bar with a wire diameter of 0.1mm (#4). <Coating fluid> An aqueous solution containing the following components and having a concentration of 5.0% calculated as polyester resin solids when the polyester resin solids are 100 parts by mass. Reference Example 22 Obtained polyester resin (A): 100 parts by mass Melamine-based crosslinking agent ("Nicalac" (registered trademark) MW12LF, manufactured by Sanwa Chemical Co., Ltd.): 5 parts by mass (solid content equivalent) Colloidal silica with a particle size of 140 nm: 2.5 parts by mass The uniaxially stretched film coated with the water-based coating agent was held with clips and introduced into an oven, where it was dried and preheated at an atmospheric temperature of 120°C. It was then continuously stretched 3.7 times in the width direction in a 120°C stretching zone. The resulting biaxially oriented (biaxially stretched) film was then heat-treated for 10 seconds in a 230°C heating zone, and then cooled from 230°C to 120°C while undergoing a 5% relaxation treatment, and then cooled to 50°C. The film was then wound up after removing both ends in the width direction to obtain a biaxially oriented polyester film (optical polyester film) with a thickness of 50 μm.
[0103] [Example 1] (Preparation of polyester film) Using the following polyester resin raw material mixture, polyester resin 1 obtained in Reference Example 1 was used to obtain an optical polyester film by the method described in Reference Example 23. The evaluation results of the obtained optical polyester film are shown in Table 3.
[0104] [Examples 2 to 19, Comparative Examples 1 to 2] An optical polyester film was obtained in the same manner as in Example 1, except that the polyester resin raw materials were as shown in Tables 1 and 2. The evaluation results of the obtained optical polyester film are shown in Tables 3 and 4.
[0105] [Table 1]
[0106] [Table 2]
[0107] [Table 3]
[0108] [Table 4] [Industrial Applicability]
[0109] The optical polyester film of the present invention is less susceptible to the generation of foreign matter, particularly internal foreign matter caused by metals, and is therefore suitable for optical applications such as displays which require high quality.
Claims
1. The number of internal defects originating from metal components with a major axis of 10 μm or more and 50 μm or less was 38 / 250 mm. 2 1. An optical polyester film, characterized in that:
2. 2. The optical polyester film according to claim 1, wherein the metal element content is from 10 ppm to 150 ppm.
3. 3. The optical polyester film according to claim 1, wherein the melt resistivity of the substrate layer is from 0.1 MΩ·cm to 10 MΩ·cm.
4. 3. The optical polyester film according to claim 1, wherein the germanium content is from 3 ppm to 100 ppm, the manganese content is from 3 ppm to 40 ppm, and the sodium content is from 4 ppm to 40 ppm.
5. 3. The polyester film for optical applications according to claim 1, having a phosphorus element content of 15 ppm or more and 70 ppm or less.
6. 3. The optical polyester film according to claim 1, which has a coating layer on at least one surface thereof.
7. 3. The optical polyester film according to claim 1, wherein the particle content is 0.01% by mass or less.
8. The optical polyester film according to claim 1 or 2, which is for phase difference transfer.
9. The optical polyester film according to claim 1 or 2, which is used as a touch panel substrate.
Citation Information
Patent Citations
Preparation of aromatic polyester
JP1988278927A
Polyester fiber for reinforcing high toughness rubber
JP1991146707A
Method of producing polyester
JP2003137992A